2019
DOI: 10.1111/odi.13238
|View full text |Cite
|
Sign up to set email alerts
|

Dental changes in children with congenital Zika syndrome

Abstract: Objective To describe oral alterations in children with congenital Zika syndrome (CZS). Methods This was a case series, whose research instrument was a structured questionnaire, associated with the use of medical record data and extra and intraoral clinical examination. Results Thirty‐two children were evaluated, the majority male (18/32%–56.3%), mean age 22 months (SD = 2.71). It was also observed that the majority of the patients (19/32%–59.4%) presented a low family income. All the children had a mean head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 27 publications
(42 reference statements)
6
43
0
Order By: Relevance
“…The most common dental changes were opacity and hypoplasia of enamel, besides microdontia and agenesis (Carvalho, Brites, et al., 2019; Carvalho, Alencar, et al., 2019; Cota et al., 2020; Gusmão et al., 2020; Oliveira, de Melo, et al., 2020; Silva et al., 2020). The most common dental changes were opacity and hypoplasia of enamel, besides microdontia and agenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The most common dental changes were opacity and hypoplasia of enamel, besides microdontia and agenesis (Carvalho, Brites, et al., 2019; Carvalho, Alencar, et al., 2019; Cota et al., 2020; Gusmão et al., 2020; Oliveira, de Melo, et al., 2020; Silva et al., 2020). The most common dental changes were opacity and hypoplasia of enamel, besides microdontia and agenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Siqueira et al, 8 analyzed the prevalence of DDE in primary dentition in children with microcephaly due to fetal exposure to the ZIKV, describing a proportion of 12.19%. Gusmão et al, 4 and Silva et al, 5 also verified the presence of opacities and hypoplasia in these children, with a prevalence of 28.10% and 30.76%, respectively.In the case of congenital syndromes, it is observed that hypoplasia is a very common DDE. 37,38 In this study, however, the greatest occurrence of changes in enamel development was represented by hypocalcification, with a prevalence of 20.59%.…”
Section: Discussionmentioning
confidence: 75%
“…However, studies focusing on this issue are still scarce in the literature. [4][5][6][7][8] As a result, the possibilities of interation with the literature are limited, making it often necessary to discuss the results from data observed in child. 23 Thus, unlike studies that analyzed a similar age range in the general population, [24][25][26][27] the occurrence of dental caries was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the severe motor and cognitive impairment, other most basic oral function altered are speech and dysphagia, which hinders their independence and eating. Multidisciplinary care including oral care is a must to provide adequate treatment and try improving quality of life in those affected by congenital ZIKV (Gusmão et al, 2019). It was not possible to evaluate case 3 with panoramic radiography due to the difficulty in reaching minimal distortion standards.…”
Section: Discussionmentioning
confidence: 99%